2012
DOI: 10.1021/pr300346c
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Identification of N-Glycosylated Proteins of Mouse Tissues and Construction of a Glycoprotein Database, GlycoProtDB

Abstract: Protein glycosylation is a common post-translational modification that plays important roles in terms of protein function. However, analyzing the relationship between glycosylation and protein function remains technically challenging. This problem arises from the fact that the attached glycans possess diverse and heterogeneous structures. We believe that the first step to elucidate glycan function is to systematically determine the status of protein glycosylation under physiological conditions. Such studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 63 publications
5
64
0
Order By: Relevance
“…Comprehensive studies of protein glycosylation (Kaji et al, 2012), phosphorylation (Lundby et al, 2012a) and acetylation (Lundby et al, 2012b) revealed thousands of differentially modified sites, opening up the possibility that PTM sites may possess substantially different sequence and spatial properties across tissues, depending on which particular enzyme catalyzes a particular modification event. The existence of compartment-specific sequence signatures for phosphorylation (Chen et al, 2014;van Wijk et al, 2014) and lysine acetylation (Choudhary et al, 2009;Kim et al, 2006;Lundby et al, 2012b;Shao et al, 2012) has already been firmly established.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive studies of protein glycosylation (Kaji et al, 2012), phosphorylation (Lundby et al, 2012a) and acetylation (Lundby et al, 2012b) revealed thousands of differentially modified sites, opening up the possibility that PTM sites may possess substantially different sequence and spatial properties across tissues, depending on which particular enzyme catalyzes a particular modification event. The existence of compartment-specific sequence signatures for phosphorylation (Chen et al, 2014;van Wijk et al, 2014) and lysine acetylation (Choudhary et al, 2009;Kim et al, 2006;Lundby et al, 2012b;Shao et al, 2012) has already been firmly established.…”
Section: Introductionmentioning
confidence: 99%
“…O-GalNAc glycoproteins are estimated to comprise 10% of proteins in the human proteome and 50% among those going through the secretory pathway (14). Two recent papers find, in various human tissues, ϳ2,500 N-glycosylated proteins each, but the sets have only partial overlap (11,15). It is likely that additional glycosylated proteins will be identified as detection methods improve.…”
Section: Pathophysiology Of Glycoproteins Glycoprotein Biosynthesis Amentioning
confidence: 99%
“…GlycoProtDB (GlycoProtein Database) (39) GlycoProtDB is a database of N-glycoproteins that have been experimentally identified in C. elegans N2 and mouse tissues (strain C52BL/6J, male). GMDB (Glycan Mass Spectral DataBase)…”
Section: Unicarbkb-unicarbkbmentioning
confidence: 99%